Re-imagining News Values and Labels of Controversies with Reference to Political Scandals. Issue 1 (2nd January 2020) - Motsaathebe, Gilbert
Abstract: Scandals involving heads of state are generally the staple diet of news media. Internationally, the Bill Clinton-Monica Lewinsky scandal and former Italian Prime Minister Silvio Berlusconi's "bunga bunga" sex escapades are some of the most memorable. In South Africa, scandals that marred former president Jacob Zuma's term of office have continued to be the centre of attention long after he resigned as president. During his presidency, Zuma became one of the most covered (reported in the news) leaders across media platforms, in South Africa and beyond. This was largely due to allegations including corruption, his relationship with the Gupta family, and misuse of government funds to renovate his private property. Evoked in the media by various labels of controversy, the media frenzy dominated headlines in South Africa at the time. This article presents an account of how journalists actively construct labels for controversy associated with newsworthiness. The article makes a theoretical link between labels of controversies and news values, and argues that these labels are, in spite of their significance, the most understudied phenomena in mainstream journalism literature today. Fifty-eight news articles were examined by means of content analysis for the labels that journalists constructed.